Pedophilia and adult-child sex: a philosophical analysis - Kershnar, Stephen (Lexington Books, 2015)
Adult-child sex, pedophilia, and hebophilia -- Disease -- Adult-child sex and backward-looking reasons -- How consent works -- Exploitation -- Adult-child sex and forward-looking reasons -- Pedophilic fantasies -- Criminalization